Kraftfahrzeugtechnische Texte in der Didaktik der deutsch-polnischen Fachübersetzung. Automotive technology texts in the didactics of the German-Polish specialist translation. - Błaszkowska, Hanka (Glottodidactica, 2016)
The article concentrates on the lexical and terminological features of the language of motorization. The analysis is based on the catalogues published by one of the leading passenger car producers in Germany and employs the perspective of specialist translation from German into Polish. The problems discussed in the article include loanwords, specialist jargon and the issues of synonymia and polysemy. The texts selected for the analysis and their specific linguistic and cultural features may serve as an interesting teaching material for specialist translation courses in philological translation studies.